Prospects of including indigenous people in urban area development towards sustainable regional development in New Clark City, Philippines documenting the processes - Sebastian, Florencia Charito I. (LIRIP: Journal of Interdisciplinary Studies, 2020)
Access online through this link: https://journals.upd.edu.ph/index.php/Lirip/article/view/8104/7074